2015
DOI: 10.1097/ccm.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Cardiomyopathy

Abstract: Stress-induced cardiomyopathy may mimic myocardial infarction and is an important condition to recognize in patients with underlying stress states, particularly neurologic injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 87 publications
2
53
0
7
Order By: Relevance
“…It was first described in Japan in 1990 by Sato et al 10. This is believed to be secondary to stress-induced catecholamine release, with subsequent stunning of the myocardium 11. Seybold et al in 2007 had reported the first case of stress-induced cardiomyopathy associated with polyglandular autoimmune type 2 syndrome in a 19-year-old man, which showed spontaneous remission with thyroxine replacement and supportive measures 12…”
Section: Discussionmentioning
confidence: 99%
“…It was first described in Japan in 1990 by Sato et al 10. This is believed to be secondary to stress-induced catecholamine release, with subsequent stunning of the myocardium 11. Seybold et al in 2007 had reported the first case of stress-induced cardiomyopathy associated with polyglandular autoimmune type 2 syndrome in a 19-year-old man, which showed spontaneous remission with thyroxine replacement and supportive measures 12…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Luckily, all 3 patients eventually either completely or partially resolved their cardiomyopathy, although the patient with a history of methamphetamine abuse showed incomplete resolution suggesting a greater degree of subclinical preexisting cardiac pathology. Despite the common belief that these clinical syndromes are relatively "benign" with regard to short-term morbidity or long-term outcome (particularly the classical "takotsubo" variety), all 3 cases involved major resource expenditure and considerable physical and emotional stress to the patient.…”
mentioning
confidence: 95%
“…A Japanese physician Dr. Sato first described Tako-tsubo cardiomyopathy at the Hiroshima City Hospital in 1990 [1][2][3][4]. In its classic form, there is aneurysmal dysfunction of the apical myocardium with dyskinesis and bulging of the ventricular wall, but with preserved function of the base of the heart.…”
Section: Editorialmentioning
confidence: 99%